STRUKTUR, MORFOLOGI, DAN AKTIVITAS BIMETALIK RU-SN/AL2O3 YANG DISINTESIS DENGAN METODA KONVENSIONAL DAN MIKROWAVE - Ari Sulistyo Rini; Shahidan Radiman; Mohd. Ambar Yarmo (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Preparation method plays an important role to produce and improve the properties of materials. Microwave-assisted preparation method has developed rapidly as a benign preparation procedure due to its fast and uniform heating mechanisms. To study the effect of preparation method, bimetallic Ru-Sn based catalyst has been synthesized by using conventional and microwave impregnation methods. In this study, microwave power used was 700 W. Metallic reduction process of ion Run+ and Snn+ were monitored using UV-Vis spectrometer. Samples were then characterized using XRD, SEM and TEM. According to TEM results, morphology of catalyst strongly depends on the preparation route and stabilizing agent. Sample with PVP (polyvinyl pyrrolidone) has better metallic nanoparticles distribution. The sample prepared by conventional method shows agglomeration of nanoparticles on the support. Catalytic activities of both samples were examined in reduction reaction of pollutant, i.e. 4-nitrophenol. The catalytic examination has shown that reaction rate of 4-nitrophenol reduction by using microwave-assisted sample has improved 3.5 times faster than conventional impregnation sample.Â Â Â Keywords: microwave, bimetallic, nanomaterial, Ruthenium-Tin, catalyst